The correlation between hyperuricemia and the risk of congestive heart failure: a cross-sectional study in Indonesia - Nadia, Farah; Julyani, Sri; Namirah, Hanna Aulia; Kartika, Irna Diyana; Nurhikmawati, Nurhikmawati (Universitas 'Aisyiyah Yogyakarta, 2025)
Congestive Heart Failure (CHF) is a leading cause of morbidity and mortality worldwide and is the second most common cause of death in Indonesia. One factor that has recently gained attention is hyperuricemia, a condition characterized by elevated serum uric acid levels, which is closely linked to the pathogenesis of cardiovascular diseases. The underlying mechanism involves increased activity of the enzyme xanthine oxidase, which triggers oxidative stress, endothelial dysfunction, and systemic inflammation, all of which contribute to the progression of CHF. This study aims to examine the relationship between serum uric acid levels and the incidence of CHF at RSUD (Regional General Hospital) I Lagaligo, East Luwu Regency. This study employed observational analytic approach with cross-sectional design. Data were collected from the medical records of 102 CHF patients treated between January 2023 and June 2024. Uric acid levels and CHF types were classified based on ejection fraction (EF). Data analysis was done using the Chi-Square test. The results showed a significant association between uric acid levels and the type of CHF (p < 0.001). Among patients with reduced ejection fraction, 83.7% had elevated uric acid levels, while 55% of patients with preserved ejection fraction had normal levels. Conclusion: There is a significant correlation between uric acid levels and CHF. Monitoring uric acid levels has the potential to serve as a clinical indicator in the evaluation and management of CHF patients.